Development of Interactive E-Module Based Android on Salt Hydrolysis Material to Improve High Order Thinking Skills - Fauzi, Agi Achmad; Purwanti, Purwanti; Lestari, Elsi Maria; Nuraini, Dewi; Noviar, Anggi (Jurnal Paedagogy, 2024)
This study aims to develop a valid and feasible Android-based interactive e-module on the subject of salt hydrolysis to improve High order thinking skills of students. The research method used is Research and Development (R&D) with the ADDIE model. The research instrument is a validation test questionnaire and feasibility test with qualitative and quantitative data analysis techniques. The results of the expert validation test obtained an average value of 81.85% with Good criteria and in the feasibility test obtained an average value of 88.18% with Good criteria. So that the interactive android-based e-module on the material of salt hydrolysis to improve High order thinking skills is feasible and practical to use in learning.